Teaching digital scholarly editing North and South in a Global Classroom - Viglianti, Raff (2021)
This presentation will introduce the pedagogy behind the 2020 course Digital Publishing with Minimal Computing / Ediciones digitales con minimal computing, designed by researchers from the University of Maryland (United States) and CONICET (Argentina) to teach minimal computing approaches to North and South American students. The class is part of the Global Classroom Initiative at the University of Maryland (UMD) with students from both UMD and from Universidad del Salvador (USAL) in Buenos Aires. The course introduces students to digital publishing and textual scholarship, with minimal computing presented as a shared set of values: use of open technologies, ownership of data and code, reduction in computing infrastructure and, consequently, environmental impact. Minimal computing can be a solution for the development of projects in the Global South, where access to infrastructure such as web hosting or even reliable and affordable Internet access is almost non-existent for humanities students and faculty. Our combined experiences presented our students with a perspective on minimal computing that is not entirely dependent on DH practices in the Global North, but rather one that is based on a shared digital commons. Our aim was emphasizing a pedagogy of multiliteracies and a polycentric DH perspective    Due to the pandemic,the 2020 class was structured as a project-based online and virtual exchange?: students attended virtual lectures and collaborated online on a minimal digital edition via Slack and GitLab, with the support of the instructors. Shared lectures and communication were mostly in English, but the syllabus included course materials (tutorials, slides) and readings in both Spanish and English. Additionally, students were able to participate either using Spanish or English in class, following GO:DH whispering methods.This was meant to both facilitate content acquisition and to expose students to contributions that are not exclusively anglo-centric in learning about Digital Humanities and Digital Scholarly Editions in particular.